2018
DOI: 10.1177/0022022117731092
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Normative Climates Strengthen the Relationship Between Identification With Europe and Tolerant Immigration Attitudes: Evidence From 22 Countries

Abstract: Europe as a supranational entity is frequently associated to inclusive and cosmopolitan values, which explains why identification with Europe generally relates to tolerant attitudes toward immigrants. However, because of major immigration movements, Europe has recently gone through demographic and social changes that have challenged its values and identity. In this context, we argue that, because national immigrant integration policies convey social norms about how citizens should deal with issues related to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…In past research, European identification has been found to buffer feelings of threat (e.g., Datler, 2016 ). Visitin and colleagues (2018) replicate this link: Identification with Europe is, across nations, related to lower prejudice toward immigrants, possibly because of the liberal and egalitarian values generally associated with Europe (see Vignoles et al, 2018 ). Yet, they also find that the national moral context affects what European identification means.…”
Section: How Does European Culture Fit Newcomers? Lessons From Europementioning
confidence: 86%
See 1 more Smart Citation
“…In past research, European identification has been found to buffer feelings of threat (e.g., Datler, 2016 ). Visitin and colleagues (2018) replicate this link: Identification with Europe is, across nations, related to lower prejudice toward immigrants, possibly because of the liberal and egalitarian values generally associated with Europe (see Vignoles et al, 2018 ). Yet, they also find that the national moral context affects what European identification means.…”
Section: How Does European Culture Fit Newcomers? Lessons From Europementioning
confidence: 86%
“…Going beyond existing research on the link between national identification and immigration attitudes, Visitin, Green, and Sarrasin (2018) examine the role of European identification amongst majority members of European nation states when predicting anti-immigrant prejudice using data from the International Social Survey Programme. They find across 22 European countries that majority individuals report identification with Europe.…”
Section: How Does European Culture Fit Newcomers? Lessons From Europementioning
confidence: 99%
“…We do not have space at this point for such a review. But suffice it to say that, despite some claims that diversity undermines the formation of a shared social identity and therefore makes groups less cohesive, less harmonious, less productive, and leaves members less satisfied (for a review, see van Knippenberg & Schippers, ), there is growing acceptance that (1) there is no simple and general relationship between diversity (including diversity due to immigration) and cohesion (Hickman, Crowley, & Mai, ; Saggar, Somerville, Ford, & Sobolewska, ), and that (2) in some circumstances diversity can increase group identification and cohesion, especially when it is consonant with group norms (van Knieppenberg, Haslam, & Platow, ; Visintin, Green, & Sarrasin, ). Clearly, though, the question of when diversity is or isn’t a problem for identification and cohesion is one that requires further clarification, and we have a responsibility not only to conduct the relevant research but also to inject the public debate so as to contest the simplifications and distortions that currently characterize that debate.…”
Section: Discussionmentioning
confidence: 99%
“…One aspect of the complexity of research on attitudes towards integration stems from the fact that it analyses public opinions towards immigrants' integration, which may society as negative, then the majority develops negative attitudes toward immigrant integration, prefers assimilation (Davies, Steele and Markus, 2008[76]; Tip et al, 2012 [77]; Van Oudenhoven, Prins and Buunk, 1998 [78]) and decreases its support for multiculturalism. However, the causal mechanism could also work the other way around.…”
mentioning
confidence: 99%